The problems of bilingualism in the linguistic communication (Eurasian Journal of Philology Science and Education, 2016)
The phenomenon of bilingualism and polylinguism is considered as one of the most developing problems of modern sociolinguistics in this article.The paper deals with the whole complex of problems that reflect the multifaceted nature of the relationship between man, society and language. The questions of language policy and planning are considered and described as the aspects of the status of the corpus building under the conditions of the new language situation.The problems of interaction and preservation of languages in the bilingual conditions are analyzed and the development of the social functions of the native language in a national-Russian bilingualism is described in the research article.
Keywords: bilingualism; multilingualism; native language; dialect; literary language.